Astrogeodetic Validation of Gravimetric Quasigeoid Models in the German Alps - First Results - Hirt, Christian; Denker, H.; Flury, J.; Lindau, A.; Seeber, G. (Harita Dergisi, 2009)
In regions with a rough topography, e.g. the European Alps, the accuracy of geoid or quasigeoid models is often reduced. For the validation and accuracy assessment of gravimetric models, astronomical levelling is a well-suited independent method. In a test area, located in the German Alps, a new astrogeodetic data set was acquired using the Hannover Digital Zenith Camera System. Vertical deflections were determined at 100 new stations (spacing about 230 m) arranged in a profile of 23 km length. Repeated observations at 38 stations in different nights reveal an observational accuracy of about 0.08. In order to precisely interpolate the vertical deflection data between adjacent stations, topographic reductions of the observed deflections are carried out using a high-resolution digital terrain model.A least squares prediction approach is applied for the interpolation of a dense profile of deflection data. Eventually, the topography effect is restored. By computing the normal correction, the deflection data is reduced to the quasigeoid domain. The accuracy of the computed astrogeodetic quasigeoid profile is estimated to be at the millimeter-level. The available quasigeoid models, namely the German Combined Geoid GCG2005, the Digital Finite Height Reference Surface DFHRS and the quasigeoid by IAPG (TU Munich), are in agreement with the high-precision astrogeodetic quasigeoid profile by about 8 mm, 20 mm and 4 mm (RMS), respectively. A comparison of the astrogeodetic profile with GPS/levelling data yielded residuals of 10 mm.